2002
DOI: 10.1111/j.1749-6632.2002.tb04392.x
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo‐Associated Theileria parva: The Risk to Cattle of Buffalo Translocation into the Highveld of Zimbabwe

Abstract: There has been an increase in the introduction of game animals, including African buffaloes, into the Highveld of Zimbabwe to establish private game reserves on condition that they are confined in separate and secured paddocks. Owing to shortages of pastures cattle were grazed in buffalo-grazed paddocks resulting in outbreaks of buffalo-derived theileriosis. This paper reports the results of epidemiological observations carried out on two game reserves to assess the risk of buffalo translocation. The infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…However, cattle entering the park is not an isolated event, an observation confirmed by other questionnaires implemented among rangers inside the KNP . While occasional wildlife-cattle contacts within the KNP should not present a risk for FMD transmission (if cattle in the area are regularly vaccinated and the vaccine provides adequate protection), they represent a risk for domestic animals contracting other diseases from wildlife, such as theileriosis (Potgieter et al, 1988;Latif et al, 2002). In addition, it also represents a risk for wildlife contracting pathogens from domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, cattle entering the park is not an isolated event, an observation confirmed by other questionnaires implemented among rangers inside the KNP . While occasional wildlife-cattle contacts within the KNP should not present a risk for FMD transmission (if cattle in the area are regularly vaccinated and the vaccine provides adequate protection), they represent a risk for domestic animals contracting other diseases from wildlife, such as theileriosis (Potgieter et al, 1988;Latif et al, 2002). In addition, it also represents a risk for wildlife contracting pathogens from domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…In another study Kundave et al, (2014) recorded, 72.52% (out of 91 samples 66 were positive) cattle and 32% (out of 25 samples 8 were positive) buffalo were positive for Theileria annulata by adopting PCR technique. Latif et al, (2002) reported, the infection rate with Theileria parasites in ticks collected from buffalo-grazed pasture was high which produced fatal theileriosis in susceptible cattle and similarly adult Rhipicephalus appendiculatus ticks artificially fed on nymphs on the buffaloes produced fatal infections in susceptible cattle. He et al, (2012) investigated, the presence and prevalence of tick-borne haemoparasites in water buffalo from the Hubei Province, South China using the reverse line blot (RLB) hybridisation assay and polygenetic analysis of the parasite 18S rRNA gene.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1a) (Walker et al, 2013) and several pathogens infecting livestock and wild ruminants in Southern Africa are transmitted by such ticks. For instance the protozoan Theileria parvas is the causative agent of Theleriosis and is mainly transmitted by Rhipicephalus appendiculatus and R. zambeziensis ticks (Latif et al, 2002) while the bacterium rickettsia Cowdria ruminantium is the causative agent of Heartwater and is transmitted by Amblyomma spp. ticks (Uilenberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%